Research Progress on the Effect of Cooling Rate on the Precipitation of Non-metallic Inclusions in Steel - Liu, Congling; Meng, Tianyu; Wang, Yan (Archives of Foundry Engineering, 2026)
This review summarizes recent experimental, thermodynamic, and kinetic studies on how cooling rate affects the precipitation and evolution of non-metallic inclusions in steel, with emphasis on oxides, sulfides, and nitrides. Across the reported literature, increasing cooling rate generally increases inclusion number density while refining particle size by shortening growth time and suppressing late-stage diffusion and compositional redistribution. For oxide inclusions, rapid cooling promotes the formation of finer and more dispersed particles, whereas slow cooling favors particle coarsening and the evolution of multi-component inclusions such as oxide-sulfide composites. For sulfide inclusions, especially MnS, higher cooling rates usually reduce average size and suppress the formation of continuous interdendritic or chain-like morphologies, while slower cooling promotes coarsening, interconnection, and composite formation with oxides or CaS-containing shells. For nitride inclusions such as TiN and AlN, rapid cooling tends to increase the population of fine particles but restricts coarsening and grain-boundary network formation. Studies show that, with increasing cooling rate, the average size of oxide inclusions in pipeline steel decreases markedly, and the mean TiN size can decrease from about 10 micrometers to about 3 micrometers. Overall, cooling rate is a key process variable because it simultaneously influences nucleation, growth, segregation, phase transformation, and interfacial reactions during solidification and subsequent cooling. A clearer understanding of these effects can support inclusion engineering, process optimization, steel cleanliness control, and property improvement in industrial steels.